2018
DOI: 10.1007/s00117-018-0471-8
|View full text |Cite
|
Sign up to set email alerts
|

Labrumpathologie des Hüftgelenkes

Abstract: Labrumpathologie des Hüftgelenkes Die Magnetresonanztomographie (MRT) von Labrumläsionen des Hüftgelenkes hat in den letzten2 Jahrzenten an Bedeutung stark zugenommen. Am besten sind die Pathologien des Labrum acetabulare mit der MR-Arthrographie (MR-ATG) zu erfassen. Neben Labrumveränderungen spielen aber auch Knorpelschädigungen, die auch mit Labrumläsionen -am chondrolabralen Übergang -einhergehen können, eine zunehmende Rolle in der Diagnostik. Mit der MR-ATG sind Einrisse und Abrisse des Labrums durch die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…By contrast, the condition of the labrum, as other studies [6,17,30] have also shown, cannot be reliably assessed using noncontrast MRIs, particularly if the radiologist does not have sufficient experience. MR arthrography also does not offer current scientific endeavours any sufficiently reliable imaging of labral and cartilage lesions and thus the option of a traction MR arthrography was developed in order to overcome the inhibited penetration of the contrast medium into the central compartment through the very closely adjacent acetabular and femoral cartilage layers [11,30]. Other authors question the need for intraarticular contrast medium in the use of 3 T devices [31].…”
Section: Equipment-related Requirementsmentioning
confidence: 94%
See 2 more Smart Citations
“…By contrast, the condition of the labrum, as other studies [6,17,30] have also shown, cannot be reliably assessed using noncontrast MRIs, particularly if the radiologist does not have sufficient experience. MR arthrography also does not offer current scientific endeavours any sufficiently reliable imaging of labral and cartilage lesions and thus the option of a traction MR arthrography was developed in order to overcome the inhibited penetration of the contrast medium into the central compartment through the very closely adjacent acetabular and femoral cartilage layers [11,30]. Other authors question the need for intraarticular contrast medium in the use of 3 T devices [31].…”
Section: Equipment-related Requirementsmentioning
confidence: 94%
“…▶ Table 8 Information from health insurance funds nationally for 06/2010-05/2011; only the combinations of OPS (3-805, 3-806, 3-826, 3-82a) or EBM (34 442 or 34 450) with the ICD-10 relevant for the hip were evaluated (see ▶ Tables 2 to 4 and are serious only in isolated cases [28]; nonetheless, patients should not undergo unnecessary exposure. Some authors therefore consider MR arthrography to be indicated only if a non-contrast MRI has been performed [30]. The possible accumulation of contrast media containing gadolinium in the central nervous system is currently being discussed [16].…”
Section: Equipment-related Requirementsmentioning
confidence: 99%
See 1 more Smart Citation